1969
DOI: 10.1126/science.166.3901.123
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonomycin: Structure and Synthesis

Abstract: Synthesis and resolution of the antibiotic phosphonomycin are described. The structure is (-)(IR, 2S)-1,2-epoxypropylphosphonic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
94
0
3

Year Published

1973
1973
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(97 citation statements)
references
References 5 publications
0
94
0
3
Order By: Relevance
“…1,2 It irreversibly inhibits MurA (UDP-N-acetylglucosamine-3-enolpyruvyltransferase), an important enzyme in bacterial cell wall biosynthesis (Scheme 1). 3 This inhibition is achieved through alkylation of an active-site cysteine residue, which performs a nucleophilic attack on the C2 atom of fosfomycin.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It irreversibly inhibits MurA (UDP-N-acetylglucosamine-3-enolpyruvyltransferase), an important enzyme in bacterial cell wall biosynthesis (Scheme 1). 3 This inhibition is achieved through alkylation of an active-site cysteine residue, which performs a nucleophilic attack on the C2 atom of fosfomycin.…”
Section: Introductionmentioning
confidence: 99%
“…Fosfomycin is a broad-spectrum antibiotic produced by some strains of Streptomyces (Christensen et al, 1969 ;Hendlin et al, 1969). Its mechanism of action was first described by Kahan et al (1974), who showed that it inhibits the enzyme UDP-N-acetylglucosamine enolpyruvyl transferase (MurA), which transfers the enolpyruvyl moiety of phosphoenolpyruvate to the 3h hydroxyl group of UDP-N-acetylglucosamine, the first committed step in bacterial peptidoglycan biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…1). 8,9) Its target is known as the enzyme forming UDP-Nacetylmuramic acid from UDP-N-acetyl glucosamine and phosphoenolpyruvic acid. 10) Thus fosfomycin is an antibiotic that inhibits bacterial peptidoglycan synthesis.…”
mentioning
confidence: 99%